Assessing the Significance and Progression of Too Small to Characterize Lesions in Hepatic CT Scans of Patients With a Cancer History: A Two‐Center Cross‐Sectional Study - Farzaneh Khoroushi; Mohammad Moeini; Lida Jarahi; Ehsan Hassannejad; Farnaz Kharghani; AmirAli Moodi Ghalibaf (Health Science Reports)
ABSTRACT Background and Aim During staging computed tomography (CT) of patients with cancer, lesions that are too small to characterize (TSTC) on the liver are frequently observed. Considering the significance of these lesions, this study aimed to evaluate the relevance and progression of TSTC lesions on hepatic CT scans in patients with a history of cancer. Method This cross‐sectional study was carried out on 50 patients with a history of cancer who underwent contrast‐enhanced abdominal CT scans. These patients were referred to Ghaem Hospital and Imam Reza Hospital, Mashhad, between March 2022 and 2023. In this study, demographic and clinical information were documented. The CT scans of all patients included in the study were evaluated by two experienced radiologists who assessed the number and size of TSTC lesions. Next, each patient was called to perform a follow‐up CT scan 6 months later. Then, the size and number of TSTC lesions were compared with the values recorded in the previous round, and their progress was evaluated. Results The study included 50 patients, of which 46% were male and 54% were female. The mean patients' age was 54.88 ± 13.60 years. In the following CT scan, among the patients with TSTC lesions, nine (18%) had liver metastases, while 41 (82%) did not. There was no significant difference between the groups with and without metastases in terms of the number of TSTC lesions (p = 0.051), the size of the largest TSTC lesion (p = 0.960), and the duration of chemotherapy (p = 0.330). However, the history of chemotherapy was statistically significant between the two groups (p < 0.001). Conclusion The incidence of metastasis in individuals with TSTC lesions was 18%, higher than that reported in similar studies. The identification of these lesions is crucial for accurate diagnosis and treatment planning.